2017
DOI: 10.1371/journal.pone.0177659
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Buzz Factor or Innovation Potential: What Explains Cryptocurrencies' Returns?

Abstract: There is an error in the equation under the subheading "Liquidity" in the Supplementary Analyses section. The correct equation is:There is an error in the third equation under the subheading "Investor Expectations and Volatility" in the Supplementary Analyses section. The correct equation is:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Less government intervention might also provide them with extra premium. (2) The more perceived value of Bitcoin the people perceive, the more government intervention people would prefer; however, the degree of the impact is less than the above situation (Wang & Vergne, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Less government intervention might also provide them with extra premium. (2) The more perceived value of Bitcoin the people perceive, the more government intervention people would prefer; however, the degree of the impact is less than the above situation (Wang & Vergne, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…4. Less restriction and supervision of exchange (PV t, 4 ): the exchange of Bitcoin is not constrained or monitored by the government (politically-motivated) (Wang & Vergne, 2017;Chuen, 2015;Yermack, 2015;European Central Bank, 2012).…”
Section: The Hypothesis and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A different yet promising approach to the study cryptocurrencies consists in quantifying the impact of public opinion, as measured through social media traces, on the market behaviour, in the same spirit in which this was done for the stock market [67]. While it was shown that social media traces can be also effective predictors of Bitcoin [68][69][70][71][72][73][74] and other currencies [75] price fluctuations, our knowledge of their effects on the whole cryptocurrency market remain limited and is an interesting direction for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Blockchain is a decentralised transaction and data management technology developed first for Bitcoin [12]. The authors [13] reinforce that the term cryptocurrency can be seen either as currency or as a 'synthetic commodity money', which 'resembles fiat money in having no nonmonetary value (but also) resembles commodity money in being not just contingently but absolutely scarce' [14]. Online and social media factors are currently related to the time intervals of cryptocurrency prices; thus it was observed 'that cryptocurrencies are prone to experience intervals of bubble-like price growth' [15].…”
Section: Blockchain and Cryptocurrenciesmentioning
confidence: 99%